Dermoscopy Assisting Diagnosis of Dermal Melanocytosis Limited to the Hand - Manni Huang; Wenfu Huang; Cuiyan Wang; Qingxiang Li; Guojing Qin (Clinical Case Reports)
ABSTRACT Acquired dermal melanocytosis (ADM) is a skin disorder characterized by the presence of melanocytes in the dermis. The face is the most common site of ADM. ADM can be difficult to diagnose when it occurs in an unusual clinical setting.